1997
DOI: 10.1046/j.1537-2995.1997.371098016441.x
|View full text |Cite
|
Sign up to set email alerts
|

The KEL24 and KEL14 alleles of the Kell blood group system

Abstract: A G659C mutation, predicting an Arg180Pro change in Kell protein, is associated with the KEL14/KEL24 allele.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0
1

Year Published

2000
2000
2013
2013

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 7 publications
0
3
0
1
Order By: Relevance
“…Recent molecular analyses indicated that these polymorphisms are due to unsynonymous base substitutions of the KEL gene (Lee, 1997). A series of Kell antigens expressed antithetically with high and low frequencies, such as KEL2 (k)/KEL1 (K), KEL4 (Kp b )/KEL3 (Kp a )/KEL21 (Kp c ), KEL7 (Js b )/KEL6 (Js a ), KEL11/KEL17 and KEL14/KEL24 (Lee et al , 1995b,c, 1996, 1997a,b). The frequencies of some Kell antigens show ethnic differences.…”
mentioning
confidence: 99%
“…Recent molecular analyses indicated that these polymorphisms are due to unsynonymous base substitutions of the KEL gene (Lee, 1997). A series of Kell antigens expressed antithetically with high and low frequencies, such as KEL2 (k)/KEL1 (K), KEL4 (Kp b )/KEL3 (Kp a )/KEL21 (Kp c ), KEL7 (Js b )/KEL6 (Js a ), KEL11/KEL17 and KEL14/KEL24 (Lee et al , 1995b,c, 1996, 1997a,b). The frequencies of some Kell antigens show ethnic differences.…”
mentioning
confidence: 99%
“…MnlI+/-DdeI+/-KEL11/KEL17(Wk a ) 13 8 1025T>C V302A HaeIII-/+ KEL10-(Ul a -)/KEL10+(Ul a +) 13 13 E494V AccI-/+ KEL12+/KEL12- 50 15 1763A>G H548R NlaIII+/-KEL13+/KEL13-(Kmod) 11,21,22 9 1106T>C L329P KEL14/KEL24 51 6 659G>C R180P HaeIII-/+ KEL18+/KEL18- 50 4 4…”
Section: R281w R281qunclassified
“…HaeIII-/+ KEL10-(Ul a -)/KEL10+(Ul a +) 13 13 1601A>T E494V AccI-/+ KEL12+/KEL12- 50 15 1763A>G H548R NlaIII+/-KEL13+/KEL13-(Kmod) 11,21,22 9 1106T>C L329P KEL14/KEL24 51 6 659G>C R180P…”
Section: T>c 2019a>gmentioning
confidence: 99%